2012
DOI: 10.3329/jname.v9i1.7416
|View full text |Cite
|
Sign up to set email alerts
|

Melting heat transfer in a nanofluid boundary layer on a stretching circular cylinder

Abstract: Abstract:A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Mukhopadhyay and Gorla [14] reported the axisymmetric laminar boundary layer flow of viscous fluid and heat transfer past a stretching cylinder in the presence of velocity slip condition and found that the velocity decreases with increasing the slip parameter. Gorla et al [15] considered the boundary layer flow of nanofluid induced by a stretching circular cylinder in the presence of melting effects. Rehman and Nadeem [16] studied the mixed convection flow of a micropolar fluid which possesses nanoparticles past a vertical slender cylinder and solved the governing problem by homotopy analysis method.…”
Section: Introductionmentioning
confidence: 99%
“…Mukhopadhyay and Gorla [14] reported the axisymmetric laminar boundary layer flow of viscous fluid and heat transfer past a stretching cylinder in the presence of velocity slip condition and found that the velocity decreases with increasing the slip parameter. Gorla et al [15] considered the boundary layer flow of nanofluid induced by a stretching circular cylinder in the presence of melting effects. Rehman and Nadeem [16] studied the mixed convection flow of a micropolar fluid which possesses nanoparticles past a vertical slender cylinder and solved the governing problem by homotopy analysis method.…”
Section: Introductionmentioning
confidence: 99%
“…Epstein and Cho [29] discussed the laminar film condensation on a vertical surface. Much later, melting heat transfer in a nanofluid boundary layer on a stretching circular cylinder was examined by Gorla et al [30]. In the study of the effect of radiation on MHD mixed convection flow from a vertical plate embedded in a saturated porous media with melting, Adegbie et al [31] reported that the Nusselt number decreases with increase in melting parameter.…”
Section: Journal Of Applied Mathematicsmentioning
confidence: 99%
“…This makes them very convection of nanofluids in porous media, and they have developed a systematic nanofluid model that incorporates the effects of Brownian motion and thermophoresis. A similarity analysis for the problem of a steady boundary-layer flow of a nanofluid on an isothermal stretching circular cylindrical surface is analyzed by Goda et al [10]. Goda et al [11] also considered the problem of mixed convective boundary layer flow of a nanofluid over a vertical wedge saturated porous medium.…”
Section: Introductionmentioning
confidence: 98%